2018
DOI: 10.1128/mbio.02419-17
|View full text |Cite
|
Sign up to set email alerts
|

Novel Segment- and Host-Specific Patterns of Enteroaggregative Escherichia coli Adherence to Human Intestinal Enteroids

Abstract: Enteroaggregative Escherichia coli (EAEC) is an important diarrheal pathogen and a cause of both acute and chronic diarrhea. It is a common cause of pediatric bacterial diarrhea in developing countries. Despite its discovery in 1987, the intestinal tropism of the pathogen remains unknown. Cell lines used to study EAEC adherence include the HEp-2, T-84, and Caco-2 lines, but they exhibit abnormal metabolism and large variations in gene expression. Animal models either do not faithfully manifest human clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(95 citation statements)
references
References 78 publications
(94 reference statements)
6
87
1
Order By: Relevance
“…Enteroid cultivation. 3D HIEs were cultured in Matrigel (BD Biosciences) and grown in HighWNT as previously described (38,41). Undifferentiated HIEs were washed with 0.5 mM EDTA in ice-cold PBS, pelleted for 5 min at 200 ϫ g, and then trypsinized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enteroid cultivation. 3D HIEs were cultured in Matrigel (BD Biosciences) and grown in HighWNT as previously described (38,41). Undifferentiated HIEs were washed with 0.5 mM EDTA in ice-cold PBS, pelleted for 5 min at 200 ϫ g, and then trypsinized.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then gently pipetted several times with a P1000 pipette before passing cells through a 40-m nylon filter to produce a single-cell solution, and approximately 2 ϫ 10 5 to 5 ϫ 10 5 cells were seeded onto polycarbonate transwell inserts (catalog number 3422; Corning) coated with collagen IV (Sigma) to form monolayers. The monolayers were incubated with 10 M ROCK inhibitor Y-27632 (Stemcell Technologies) for 24 h and then grown in differentiation medium (38,41) for 4 days. Differentiation medium was changed every other day prior to infection.…”
Section: Methodsmentioning
confidence: 99%
“…Previous data had shown that ExPEC adheres less to intestinal enteroids compared to the diarrhea-causing pathogen Enteroaggregative Escherichia coli (EAEC) (data not shown). EAEC adheres to HIEMs robustly in an aggregative, mesh-like pattern and similar to phage ES17 utilizes heparan sulfate as a receptor to bind these human colonic cells (Rajan et al, 2020, paper in review) Rajan et al, 2018). Thus, EAEC serves as an ideal E. coli strain to test the hypothesis that phage targeting HSPGs can increase killing.…”
Section: Es17 Binds To the Surface Of Human Intestinal Enteroids (Heims)mentioning
confidence: 99%
“…For this experiment we pre-coated HIEMs with phage ES17, washed, as detailed above, then infected with EAEC strain 042. HIEMs were fixed and stained using a Geimsa-Wright stain to visualize cells and bacteria, as previously described (Rajan et al, 2018). Infected HIEMs showed robust bacterial adhesion to cells with an aggregative phenotype (Figure 5Cii, red arrows).…”
Section: Es17 Binds To the Surface Of Human Intestinal Enteroids (Heims)mentioning
confidence: 99%
“…In addition to commensal bacteria, pathogenic bacteria Escherichia coli [90][91][92][93] , Salmonella 94-96 , Clostridium difficile 97 , and Cryptosporidium 98 can be incorporated into intestinal organoid systems to understand the effects of bacterial pathogens on the intestinal epithelium. Colonization of enterohemorrhagic E. coli (EHEC) in a human colonic organoid monolayer decreased intestinal mucus and destroyed microvilli, facilitating bacterial access to and infection of epithelial cells 93 .…”
Section: Intestinal Organoids That Incorporate Microbiota and Virusesmentioning
confidence: 99%